2018
DOI: 10.1016/j.jalz.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory function and neurocognitive outcomes in old age: The Atherosclerosis Risk in Communities Neurocognitive Study

Abstract: An impaired sense of smell may serve as a readily accessible early marker of neurodegeneration and improve upon the prevailing delayed diagnoses and underascertainment of MCI/dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…1 PRISMA flowchart of selected studies included in this systematic review [45] Covariates Age, sex and education were included as a covariate in each of the studies. As shown by Table 6, apolipoprotein E (APOE) e4 was considered in three of the nine studies [48][49][50]. Kreisl et al found no correlation between UPSIT scores and APOE e4 status (OR 1.75; 95% CI 0.56, 5.44; p = 0.3352), and also that APOE e4 status was not significantly higher in MCI in comparison to HC (p = 0.4488) [49].…”
Section: Cultural Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…1 PRISMA flowchart of selected studies included in this systematic review [45] Covariates Age, sex and education were included as a covariate in each of the studies. As shown by Table 6, apolipoprotein E (APOE) e4 was considered in three of the nine studies [48][49][50]. Kreisl et al found no correlation between UPSIT scores and APOE e4 status (OR 1.75; 95% CI 0.56, 5.44; p = 0.3352), and also that APOE e4 status was not significantly higher in MCI in comparison to HC (p = 0.4488) [49].…”
Section: Cultural Biasmentioning
confidence: 99%
“…Woodward et al found that APOE e4 status was higher in both MCI and AD when compared to HC; however, odour identification deficiency was independent from APOE e4 status [48]. Furthermore, smoking is included as a covariate in four articles [46,48,50,51] Medication Use of Participants Table 7 shows that only three of the nine included articles considered medication use in their study design or as a covariate [49,50,52], and one stated lack of consideration as a limitation [48]. Even when medication use was included in the study design, there was typically only consideration of a specific type, such as psychotropics, and did not account for all medications a participant may be taking.…”
Section: Cultural Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory processes such as smelling, hearing, and vision are naturally declining to some extent in aged humans but have been shown to be prodromal of dementia [9,10]. Worsening of olfaction impairments are subsequently predictive of MCI developments and may predict the progression to AD [80][81][82][83]. Several clinical studies have demonstrated early tau pathology in the anterior OB circuit, confirming that dysfunctional olfaction may precede cognitive loss [67,69,84], which indicates a concrete potential for the use of olfaction circuitry function in diagnosis and translational research.…”
Section: Translational Perspectivementioning
confidence: 99%